The Problems of the Legal Regulation of the Labor Migration in the Draft Treaty of the Eurasian Economic Union (International relations and international law Journal, 2016)
The article deals with the problems of the international legal regulation of the labor migration in the Draft Treaty of the Eurasian economic union. The authors analyze treaty base, which operated before the customs union and the implementation aspects of the problem in the draft agreement on the establishment of the Eurasian Economic Union. An important aspect in the creation of this kind of association, of course, is the freedom of movement of labor and the creation of a common labor market. Creating a common labor market in the EEC is still at an early stage, held the harmonization of legal frameworks. Violations of labor law and social and labor rights of migrant workers are still taking place. The most serious was the problem of creating the necessary conditions and the implementation of labor protection of migrant workers. This defines the important role of processes of the universalization and unification the of labor law in the partner countries. A significant aspect of integration is the convergence of legal standards and orientation law on international legal acts.
Keywords: Economic Union; labor migration; contract of employment; migrant worker; employer